Body mass changes and ad libitum fluid replacement in elite futsal players during official competition - Garcia Jimenez, J. V.; Yuste, J. L.; Garcia Pellicer, J. J.; Hellin Martinez, M. (Journal of Human Sport & Exercise, 2015)
The aim of this study was to calculate sweat loss, voluntary fluid replacement and levels of dehydration in elite futsal players during official competition. Measurements were made in 12 male elite futsal players during six official matches in the Spanish First Division (22-26 ºC and relative humidity 32-42.33%). Participants were weighed before the warm up and they reweighed immediately after the games. Sweat loss was assessed through changes in body mass after taking into account fluid intake and urine loss. To analyze this data the statistics used were descriptive and non parametric. Mean sweat loss of players amounted to 2.29 litres (s = 0.73). Mean fluid intake was 1.5 litres (s = 0.74), replacing 68.37% (s = 32.44) of total fluid loss. Players incurred a body mass deficit of 1.04% (s = 1.06), which is not seen as affecting their performance. There were no significant difference in sweat lost replaced and dehydration in relation to analyzed match (P > 0.05). There is a correlation between game time and body mass loss (r = 0.323, P = 0.016). From the results, we conclude that the level of hydration in studied players can be seen to maintain itself through a correct level of fluid intake. However, these measurements allow an individualisation of player hydration strategies, not taking exclusively into account game time.